2016
DOI: 10.1016/j.chempr.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Phenomena at Perovskite/Electron-Selective Contact Interface as Interpreted from Photovoltage Decays

Abstract: Bisquert and colleagues demonstrate the impact of positive charge accumulation at the electron contact of perovskite solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
205
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(243 citation statements)
references
References 46 publications
21
205
0
Order By: Relevance
“…It is important to recognize that along with the photo generation, transportation, and recombination of charge carriers, the mobile ions and charge defects can also move and cause the screening of a builtin electric field [19][20][21][22]. Recent studies have shown that the accumulation of the ions and vacancies at interfaces changes the interfacial charge concentration and recombination rates, as well as the net photovoltage by setting up an electrostatic potential in addition to the built-in potential [23][24][25]. Since the electrostatic and built-in potentials have the same polarity (backward scan), the net open circuit voltage (VOC) of PSC devices is the sum of these potentials [24,26].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to recognize that along with the photo generation, transportation, and recombination of charge carriers, the mobile ions and charge defects can also move and cause the screening of a builtin electric field [19][20][21][22]. Recent studies have shown that the accumulation of the ions and vacancies at interfaces changes the interfacial charge concentration and recombination rates, as well as the net photovoltage by setting up an electrostatic potential in addition to the built-in potential [23][24][25]. Since the electrostatic and built-in potentials have the same polarity (backward scan), the net open circuit voltage (VOC) of PSC devices is the sum of these potentials [24,26].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Recent studies have shown that the accumulation of the ions and vacancies at interfaces changes the interfacial charge concentration and recombination rates, as well as the net photovoltage by setting up an electrostatic potential in addition to the built-in potential [23][24][25]. Since the electrostatic and built-in potentials have the same polarity (backward scan), the net open circuit voltage (VOC) of PSC devices is the sum of these potentials [24,26]. A generalized single diode model of a PSC, including the built-in and electrostatic potential formed due to the accumulation of ions and charges, is placed in a model previously discussed by Gottesman and others (Figure 1b) [24,26,27].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…3,27,28 Great efforts have been made to develop deposition methods that are able to obtain high-quality perovskite crystals. Typically, perovskite layers with large grain size, uniform morphology and appropriate composition will possess low defect density and show restricted ion migrations, which enable hysteresis-free/less devices with various architectures.…”
Section: Characterization Of C-tio 2 Layermentioning
confidence: 99%
“…The results will be interpreted in terms of the interaction of charge accumulation and recombination effects, following previous observations of transient decays dependence on slow ionic kinetics. 27 The analysis of photovoltage changes provides a general standpoint for understanding of the operation of contacts in the perovskite based photovoltaics.…”
Section: Introductionmentioning
confidence: 99%